The lost airman : a true story of escape from Nazi-occupied France - Meyerowitz, Seth; Stevens, Peter F., 1955- (Berkley Caliber, 2016)
Documents the story of a World War II American Air Force turret-gunner who was one of two escapees when his team's plane was shot down near Cognac in 1943, tracing his harrowing six-month flight to safety across the Pyrenees under constant pursuit by the Gestapo.